Hubungan Antara Kepercayaan Diri Dengan Body Image Pada Perempuan Dewasa Awal Yang Menggunakan Produk Perawatan Tubuh Di Apotek UMY - Nisa Nur Lathifah; Eni Rohyati (LPPM Universitas Proklamasi 45, 2025)
This study aims to examine the relationship between self-confidence and body image among early adult women using body care products at Apotek UMY. The participants were 100 female respondents aged 18–25 years, selected using purposive sampling. The instruments used were the self-confidence scale (44 valid items, α = 0.936) and the body image scale (38 valid items, α = 0.941). Data were analyzed using Pearson correlation. The results indicated a significant positive correlation between self-confidence and body image (r = 0.585; p = 0.000). This finding suggests that the higher the level of self-confidence, the more positive the body image. The results support previous studies and highlight the role of self-confidence as a crucial factor in the development of a healthy body image. The study is expected to provide practical implications for early adult women to strengthen self-acceptance and confidence beyond societal beauty standards.